Forgiveness-Hope Relationships Considering the Risk of Depression: Samples from Public School Students in A Religious Country - Rahmandani, Amalia; Amaranggani, Anindhita Parasdyapawitra (Universitas Muhammadiyah Yogyakarta, 2023)
This study described forgiveness-hope relationships among normal adolescents and those at high risk of depression in Indonesia, which is considered a religious country. This quantitative study involved 713 adolescents from a state vocational school in Semarang, obtained purposively in both sample groups (male = 64.1%; nHigh risk = 42; nNormal = 671). Measurements used the DASS-Depression, Forgiveness Scale, and State Hope Scale. Data distributions supported non-parametric tests. Statistical analysis particularly used Spearman's Rho correlation. Additional analyses used descriptive statistics and Mann-Whitney U. The study resulted in a significant positive correlation between forgiveness and hope in each sample group; the correlation coefficient was greater in the high-risk sample (rxy normal = .184, p .001; rxy high-risk = .413, p = .006). When the correlation in the normal sample was significant for each gender, the correlation in the male high-risk sample was not significant alone (rxy = .374, p = .104). Specifically, both genders of the high-risk sample benefited from their pathways but not the agency subscale. Among all the forgiveness dimensions in the high-risk sample, only forgiveness of situations contributed to hope (rxy = .437, p = .004), unlike the normal sample, which had the least contribution (rxy = .109, p = .005). The results indicated that forgiveness may encourage better hope in more depressed adolescents, especially female adolescents. Targeting forgiveness in situations is the primary goal for depressed adolescents, thus encouraging efforts to find coping strategies regardless of their capacity. Further experimental studies can be suggested.